Pangamanan Pesan Menggunakan Kriptografi Caesar Cipher dan Steganografi EOF pada Citra - H, Hermansa; Umar, Rusydi; Yudhana, Anton (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Security in the protection of sending messages is a matter that must be considered, because the more the development of the age, the more sophisticated the technology. So that security in sending messages and data communication should be of more concern. Therefore we need a method or algorithm that can protect the message to be sent to the recipient of the message. The algorithm that can be used in encrypting is Caesar Cipher, as a cryptographic coding technique for messages so that messages that look difficult to read and solve. As for the method of inserting messages on encrypted image media using the End of File (EOF) steganography method, which is the method used directly at the end of the file. In the work of securing techniques of messages on this system, using various sizes of images or images that will be inserted a coded secret message or encryption whose capacity is not much different from the photos or images to be used. The conclusion of this study is that the application of the Caesar Cipher Algorithm can be used as a message security technique even though the algorithm is so simple but the level of security is assisted by the End of File (EOF) method to insert the encryption results from the Caesar Cipher algorithm so that the security level it has is sufficient to protect message information to be safe from eavesdroppers or hackers of the message that is not responsible or as a protection of data held.